10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Although preventable oral diseases are still very common among school-aged children worldwide, dental caries remains a significant public health concern despite decades of school-based prevention approaches. Oral hygiene habits formed during childhood are essential to long-term oral and general health. This study assessed how well various school-based oral health education strategies improved kids' oral hygiene, during the education and in long term. Controlled interventional studies involving healthy children in school settings were used in a quantitative systematic review and meta-analysis. Teachers, dental professionals, or other educational methods were used to deliver the educational programs. Standardized oral hygiene indices were used to compare the non-educated control groups before and after the intervention. Artificial intelligence-assisted screening was used to improve the efficiency and consistency of the study selection process. While alternative educational approaches showed more limited effects, teacher-led and health care worker-led interventions were linked to significant short-term improvements in oral hygiene. However, over longer follow-up periods, improvements were not consistently maintained. These results show how crucial schools are as venues for promoting oral health, but they also suggest that traditional education-focused interventions might not be enough to bring about long-lasting behavioral change. To achieve long-lasting population-level oral health benefits, program design, implementation, and integration into larger health promotion strategies may need to be strengthened.